Tradisi Marsiadapari Masyarakat Batak Toba dalam Perspektif Teori Solidaritas Emile Durkheim - Oktavia, Nia (Sekolah Tinggi Diakones HKBP, 2023)
This paper aims to discuss the mutual cooperation tradition (marsiadapari), Marsiadapari is a system of mutual cooperation carried out by a group of people in an activity. This activity is generally carried out by a group of people in an activity carried out on agricultural land, starting from land preparation to harvesting. The focus of this research is to look at the marsiadapari tradition which has been degraded by the advancement of civilization in the industrial revolution era. The location of this research is in Southeast Aceh District, Semadam District, precisely in Lawe Kinga Village. By using the perspective of Emile Durkheim and qualitative research methods with a descriptive approach. Data were obtained through a literature review by utilizing library sources to obtain this research data, through telephone interviews and using various written sources such as books, articles, journals and documents relevant to the study in this paper.